2022
DOI: 10.3389/fcimb.2022.804644
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic, Prognostic, and Therapeutic Roles of Gut Microbiota in COVID-19: A Comprehensive Systematic Review

Abstract: IntroductionThe Coronavirus Disease 2019 (COVID-19) pandemic caused by Severe Acute Respiratory Coronavirus 2 (SARS-CoV-2) emerged in late December 2019. Considering the important role of gut microbiota in maturation, regulation, and induction of the immune system and subsequent inflammatory processes, it seems that evaluating the composition of gut microbiota in COVID-19 patients compared with healthy individuals may have potential value as a diagnostic and/or prognostic biomarker for the disease. Also, thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 142 publications
3
64
0
1
Order By: Relevance
“…Increase in viral-induced cytokines may compromise intestinal integrity, facilitating the entry of bacteria and metabolites into circulation. Such dysbiosis triggers the innate immune responses, causing pulmonary dysfunction and secondary infections [77]. Furthermore, integrative multi-omics profiling reveals that subjects with GI complications exhibit unique T cell signature during COVID-19 recovery [20].…”
Section: Gut Microbiotamentioning
confidence: 99%
“…Increase in viral-induced cytokines may compromise intestinal integrity, facilitating the entry of bacteria and metabolites into circulation. Such dysbiosis triggers the innate immune responses, causing pulmonary dysfunction and secondary infections [77]. Furthermore, integrative multi-omics profiling reveals that subjects with GI complications exhibit unique T cell signature during COVID-19 recovery [20].…”
Section: Gut Microbiotamentioning
confidence: 99%
“…Fecal calprotectin levels were elevated in patients infected with SARS-CoV-2, confirming that SARS-CoV-2 causes intestinal inflammation [83]. A recent comprehensive systematic review confirmed that the most common alteration in the bacterial composition of patients with COVID-19 was a depletion in the genera Ruminococcus, Alistipes, Eubacterium, Bifidobacterium, Faecalibacterium, Roseburia, Fusicathenibacter, and Blautia, as well as the enrichment of Eggerthella, Bacteroides, Actinomyces, Clostridium, Streptococcus, Rothia, and Collinsella [84]. Changes to the gut microbiome composition and function affect the respiratory tract through the common mucosal immune system, and respiratory dysbiosis also affects the digestive tract through immune regulation [85].…”
Section: Sars-cov-2 and Gut Microbiomementioning
confidence: 93%
“…Viruses 2022, 14, x FOR PEER REVIEW 7 of 17 function affect the respiratory tract through the common mucosal immune system, and respiratory dysbiosis also affects the digestive tract through immune regulation [85]. Alterations in the gut microbiome are associated with severity and poor prognosis in patients with COVID-19, such as increases in Bacteroides, Parabacteria, Clostridium, Bifidobacterium, Ruminococcus, Campylobacter, Rotella, Corynebacterium Pseudomonas, Megacoccus, Enterococcus, and Aspergillus, as well as reductions in Roseburia, Eubacterium, Lachnospira, Faecalibacterium, and Firmicutes/Bacteroidetes ratios [84]. The fungal gut microbiota of patients with severe/critical COVID-19 was characterized by decreased diversity, richness, and evenness, and increased relative abundance of Ascomycota phylum compared with non-severe COVID-19 [86].…”
Section: Host Immune Response Induced By Sars-cov-2mentioning
confidence: 99%
“…Similarly, there is evidence that altered gut microbiota composition has a crucial role in the severity and virulence of bacterial and viral infections [96]. Many studies have reported gut dysbiosis among COVID-19 patients and noted that it would be a major contributor to poor outcomes [97].…”
Section: Gut Microbiotamentioning
confidence: 99%
“…Finally, it was reported by Zuo et al that Coprobacilum spp., Clostridium Ramosum, and Clostridium hathewayi were associated with more severe diseases [20]. One similar systematic review stated that Bi dobacterium, Bacteroides, Corynebacterium, Ruminococcus, Parabacteroides, Campylobacter, Clostridium, Ruminococcus, Rothia, Enterococcus, Megasphaera, Enterococcus, and Aspergillus had high abundance among severe COVID-19 patients while, Lachnospira, Roseburia, Faecalibacterium, Eubacterium, and Firmicutes/Bacteroidetes ratio had declined among severe COVID-19 cases [97]. Other similar studies also have noted the higher abundancy of opportunistic pathogens including; Veilonella, Streptococcus, Rothia, and Actinomyces [20,88], and declining levels of bene cial commensal bacteria such asRoseburia, Agathobacter, Fusicatenibacter, and Ruminococcaceae among moderate to severe COVID-19 patients [20].…”
Section: Severitymentioning
confidence: 99%